2022
DOI: 10.3389/fneur.2022.886171
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implant Electrode Impedance as Potential Biomarker for Residual Hearing

Abstract: Introduction and ObjectivesAmong cochlear implant candidates, an increasing number of patients are presenting with residual acoustic hearing. To monitor the postoperative course of structural and functional preservation of the cochlea, a reliable objective biomarker would be desirable. Recently, impedance telemetry has gained increasing attention in this field. The aim of this study was to investigate the postoperative course of the residual acoustic hearing and clinical impedance in patients with long electro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…Previous studies have published mixed results regarding the link between impedances and electrode positioning. For example, some studies reported higher impedances at the apex of the cochlea compared to the base ( 25 , 26 , 28 ), while Saunders et al ( 27 ) reported an inverse relationship. Studies that linked impedance measurements to electrode-to-modiolus distance did not find a clear relationship ( 22 , 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have published mixed results regarding the link between impedances and electrode positioning. For example, some studies reported higher impedances at the apex of the cochlea compared to the base ( 25 , 26 , 28 ), while Saunders et al ( 27 ) reported an inverse relationship. Studies that linked impedance measurements to electrode-to-modiolus distance did not find a clear relationship ( 22 , 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it might indicate variations in the tissues surrounding the electrode and its resistive properties. Some studies have reported higher impedances for apical contacts than basal contacts ( 25 , 26 ), while others found an inverse relationship ( 27 ). No clear relationship is found between impedances and distance to the modiolus ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wimmer and colleagues observed higher impedances measured one month after surgery and their gradual decrement over time. Electrode contacts inserted more apically exhibited higher impedances, but basal electrodes maintained higher impedance for longer [ 26 ]. A similar trend was recorded in this study in patients No.…”
Section: Discussionmentioning
confidence: 99%
“…3. The former was not uncommon in the postoperative period and already described as related to inner ear events leading to a loss of residual hearing and dizziness [ 26 ]. The second could be related to possible dilatation or scar tissue formation due to the removal of the posterior part of the cochlear basal turn.…”
Section: Discussionmentioning
confidence: 99%
“…ECochG can also be useful in the post-operative phase, where patients may lose residual cochlear function 21,22 . Most commonly, such losses occur during the first six to twelve months after implant surgery [23][24][25] due to different intra-cochlear factors (e.g., immune response to the electrode, intracochlear inflammatory reactions, and intracochlear scar tissue formation) 14,26,27 . However, the underlying mechanisms remain poorly understood and require further research 24 .…”
Section: Background and Summarymentioning
confidence: 99%